IMPACT OF SOCIAL MEDIA ON PURCHASE INTENTION OF YOUTH TOWARDS GREEN COSMETIC PRODUCTS - 1Aiswariya Chandel, 2Dr. Ankita Jain (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This study delves into the influence of social media on the environmentally conscious purchasing behavior of youth, specifically focusing on green cosmetic products. Utilizing a mixed-methods approach, including surveys and interviews, the research explores the correlation between social media exposure, attitudes toward sustainability, and purchase intentions. Key findings reveal that urban and rural youth, particularly females, display a strong preference for green beauty products. Influencers with cosmetology expertise significantly impact consumer choices. The study’s insights provide valuable guidance for green cosmetic brands in crafting effective marketing strategies, emphasizing the importance of aligning with environmental consciousness to engage the youth demographic successfully. Additionally, the research contributes to a deeper understanding of the psychological and social factors influencing sustainable consumption in the beauty industry.